The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1590/s0100-879x2003000600007
|View full text |Cite
|
Sign up to set email alerts
|

A randomized double-blind study of the short-time treatment of obese patients with nonalcoholic fatty liver disease with ursodeoxycholic acid

Abstract: In order to determine the effect of ursodeoxycholic acid on nonalcoholic fatty liver disease, 30 patients with body mass indices higher than 25, serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST) or γ-glutamyltransferase (γ-GT) at least more than 1.5 times the upper limit of normality, and hepatic steatosis demonstrated by ultrasonography were randomized into two groups of 15 patients to receive placebo or 10 mg kg -1 day -1 ursodeoxycholic acid for three months. Abdominal compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 33 publications
(50 reference statements)
0
19
0
Order By: Relevance
“…Seven RCTs (639 participants, 21% diabetic; three RCTs with post-treatment histology, five RCTs with a low risk of bias) evaluated UDCA in NAFLD (ESM Table 5) [82][83][84][85][86][87][88].…”
Section: Ursodeoxycholic Acid (Udca)mentioning
confidence: 99%
“…Seven RCTs (639 participants, 21% diabetic; three RCTs with post-treatment histology, five RCTs with a low risk of bias) evaluated UDCA in NAFLD (ESM Table 5) [82][83][84][85][86][87][88].…”
Section: Ursodeoxycholic Acid (Udca)mentioning
confidence: 99%
“…5). [45][46][47] Two of these RCTs assessed post-treatment-histology, finding no benefit over placebo, but the effect of high-dose UDCA on liver histology is unknown ( Figs. 2-4; Table 1).…”
Section: Ursodeoxycholic Acidmentioning
confidence: 99%
“…In three RCTs (113 participants, 1 RCT with quality score !7), UDCA for 1.5 to 6 months did not significantly improve ALT levels or radiological steatosis [47][48][49] (Fig. 5, Table 1).…”
Section: Ursodeoxycholic Acidmentioning
confidence: 99%
“…So far, four randomized trials with 279 patients have been performed to evaluate the efficacy of ursodeoxycholic acid in the treatment of NAFLD (Santos et al, 2003;Lindor et al, 2004;Méndez-Sá nchez et al, 2004;Ersöz et al, 2005). Although improvement in liver function parameters was reported in individual trials, a metaanalysis showed that ursodeoxycholic acid treatment was not associated with significant differences in mortality or liver function tests (Orlando et al, 2007).…”
Section: Other Approachesmentioning
confidence: 99%